On Stochastic Analysis of the Quantities of Information in Economics - Angli Liu (International Journal of Electrical and Computer Engineering (IJECE), 2012)
In this paper, the definition of information and data are presented with examples illustrating the differences between them. To articulate the value of information, the definition of quantities of information, based on information theory, generally considered to be founded by Claude Shannon, has been quoted. In addition, with corresponding mathematical derivations, specific examples are employed to manifest the factors that make information valuable. At last, we have a multifold discussion on the importance of information to economics.DOI:http://dx.doi.org/10.11591/ijece.v2i6.1795